Roles of ribosomal RNA in health and disease - Johnston, Ryan; Aldrich, Anne; Lyons, Shawn M. (Frontiers in RNA Research, 2024)
Ribosomes are amongst the most ancient molecular machines in cells, showing conservation from the simplest prokaryotes to humans. Ribosomes are an assembly of ribosomal (r)RNA and ribosomal proteins, but the rRNA comprises most of the mass of the ribosome and performs key enzymatic tasks. In humans, rRNA undergoes a laborious maturation that involves multiple processing steps and the deposition of chemical modifications. The correct processing and modification of rRNA ensures the proper function of the mature ribosome. Disturbance of these processes may lead to human disease. Understanding the role of rRNA in protein synthesis and the consequences of its dysregulation is key to deciphering and mitigating the emergence of pathological states in human biology.